A Mutation Upstream of the rplN-rpsD Ribosomal Operon Downregulates Bordetella pertussis Virulence Factor Production without Compromising Bacterial Survival within Human Macrophages - Novák, Jakub; Jurnečka, David; Linhartová, Irena; Holubová, Jana; Staněk, Ondřej; Štipl, Daniel; Dienstbier, Ana; Večerek, Branislav; Azevedo, Nayara; Provazník, Jan; Beneš, Vladimír; Šebo, Peter (mSystems, 2020)
The BvgS/BvgA two-component system controls expression of ∼550 genes of Bordetella pertussis, of which, ∼245 virulence-related genes are positively regulated by the BvgS-phosphorylated transcriptional regulator protein BvgA (BvgA∼P). We found that a single G-to-T nucleotide transversion in the 5'-untranslated region (5'-UTR) of the rplN gene enhanced transcription of the ribosomal protein operon and of the rpoA gene and provoked global dysregulation of B. pertussis genome expression. This comprised overproduction of the alpha subunit (RpoA) of the DNA-dependent RNA polymerase, downregulated BvgA and BvgS protein production, and impaired production and secretion of virulence factors by the mutant. Nonetheless, the mutant survived like the parental bacteria for >2 weeks inside infected primary human macrophages and persisted within infected mouse lungs for a longer period than wild-type B. pertussis These observations suggest that downregulation of virulence factor production by bacteria internalized into host cells may enable persistence of the whooping cough agent in the airways.IMPORTANCE We show that a spontaneous mutation that upregulates transcription of an operon encoding ribosomal proteins and causes overproduction of the downstream-encoded α subunit (RpoA) of RNA polymerase causes global effects on gene expression levels and proteome composition of Bordetella pertussis Nevertheless, the resulting important downregulation of the BvgAS-controlled expression of virulence factors of the whooping cough agent did not compromise its capacity to persist for prolonged periods inside primary human macrophage cells, and it even enhanced its capacity to persist in infected mouse lungs. These observations suggest that the modulation of BvgAS-controlled expression of virulence factors may occur also during natural infections of human airways by Bordetella pertussis and may possibly account for long-term persistence of the pathogen within infected cells of the airways.
Keywords: two-component regulatory systems; Bordetella pertussis; host-pathogen interactions; macrophages; intracellular bacteria; virulence regulation